Análise imunológica dos efeitos dos cimentos MTA, Bio-C Repair e Bio-C Repair íon+ nas respostas de macrófagos inflamatórios de murino - Francielen Oliveira Fonseca (2022)
The improvements achieved in the physicochemical properties of endodontic materials allowed the use of repair materials in clinical situations considered critical. The so-called bioceramics, derived from MTA, showing good biocompatibility and bioactivity, have become an effective solution. These materials have improved clinical properties, exhibiting excellent consistency and handling, as well as good working and setting time. These types of cement are still evolving, and companies have been investing in improvements in their compositions to enhance their bioactive properties. This study aimed to evaluate the Bio-C Repair bioceramic cement (Angelus, Londrina, Paraná, Brazil) and its potential successor, the Bio-C Repair Íon+ (Angelus, Londrina, Paraná, Brazil), as well as the MTA (Angelus, Londrina, Paraná, Brazil). The Animal Use Ethics Committee (CEUA) of the Federal University of Minas Gerais (UFMG) approved the study (350/2019). Such bioceramics were evaluated in macrophage responses. The experiments were carried out in the Gnotobiology and Immunology laboratory of the Institute of Biological Sciences (ICB) of the UFMG. Murine macrophages obtained from C57BL/6 mice were used to evaluate cell viability (by the MTT method), cell adhesion, phagocytosis capacity (in the presence of the yeast S. boulardii), and in the detection of the production of Reactive Oxygen Species (ROS) in the absence and presence of Zymosan A (from Saccharomyces cerevisiae), as well as in the presence and absence of types of cement. Inflammatory macrophages were obtained by injecting sterile 3% thioglycolate broth into the animals' peritoneum. After aspirating, the macrophages were centrifuged, and the final cell concentration was adjusted according to each proposed assay: viability and adherence (1x106 cells/mL), phagocytosis, and ROS assay (5x105 cells/mL). The materials were manipulated under laminar flow when inserted into sterile capillaries. The cell viability results showed a significant difference in the 24-hour culture, treated with Bio-C Repair Ion+, to the control group. The phagocytosis and cell adhesion assays showed no statistically significant difference between the groups. The analyses showed expressive ROS levels when the cells were treated in the presence of Zymosan A. In the presence of this stimulus, the Bio-C Repair Ion+ showed a significant difference between all other bioceramics and the control group. The results were analyzed by the ANOVA test (P<0.05), comparing the experimental groups and the control group. It is concluded that the new repair material Bio-C Repair Ion+ has biocompatibility actions almost similar to Bio-C Repair and MTA. The differences observed with Bio-C Repair Ion+ regarding cell viability and ROS production may be related to the metallic ion's composition.